LSD1 and HY5 antagonistically regulate red light induced-programmed cell death in Arabidopsis - Chai, Tingting; Zhou, Jun; Liu, Jian; Xing, Da (Frontiers in Plant Science, 2015)
Programmed cell death (PCD) in plant is triggered by abiotic and biotic stress. Light-dependent PCD is unique to plants. Light-induced PCD also requires reactive oxygen species (ROS) and salicylic acid (SA). In this study, lesion simulating disease1 (LSD1) and elongated hypocotyl 5 (HY5) perform opposite roles to regulate excess red light (RL)-triggered PCD associated with ROS and SA production. Under RL, the lsd1 mutant released more ROS and SA and displayed a stronger cell death rate than the hy5 mutant. It was shown that active LSD1 converted into inactive form by changing the redox status of the plastoquinone pool, and HY5 interacted with phytochrome B (phyB) to promote PCD in response to RL. LSD1 inhibited the enhanced disease susceptibility 1 (EDS1) expression by upregulating SR1, whereas HY5 enhanced the enhanced EDS1 expression by binding to the G-box of the EDS1 promoter. This study suggested that LSD1 and HY5 antagonistically modulated EDS1-dependent ROS and SA signaling; thus, PCD was mediated in response to RL.